Physical Properties of Pure Gold Nanoparticles and Gold Doped ZnO Nanoparticles Using Laser Ablation in Liquid For Sensor Applications - Nabaa Hassan; Makram Fakhri; Evan Salim (Engineering and Technology Journal, 2022)
In this paper, the effect of using laser ablation of pure gold targets to obtain gold Nano rods and for pure zinc targets to obtain zinc oxide nanoparticles was studied separately in ethanol using an Nd:YAG laser tattoo removal (nanosecond pulses) and then mixing the resulting mixtures to obtain gold dopant with zinc oxide. Transmission electron microscopy (TEM), (XRD) X-Ray Diffraction and the optical properties were used to characterize the pure gold Nano rods, ZnO nanoparticles, and Au doped ZnO nanoparticles. Based on XRD and TEM, the results revealed the properties of the produced gold Nano roads. The obtained results indicated that the gold Nano rods produced by the 1064nm laser have superior optical, structural, and morphological properties and can be used in different sensors.